Manajemen Talenta Dan Pengembanag Karier Pengaruhnya Terhadap Kinerja Karyawan - M. Naely Azhad; LIsa Anggraeni (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – The human resourcess management aims to improve employee performance, so talent management and career development are increasingly important for an organization. Aim – This study aims to examine the effect of talent management and career development on employee performance. This study can contribute to improving employee performance. Design/ Methodology/ Approach - The object of the research is the employees of the Dinas Pertanian Ketahanan Pangan dan Perikanan Kabupaten Bondowoso, amounting to 200 people. Hypothesis testing was carried out by using the SPSS program t test. Results and Discussion - The results show that the talent management variable has a significant effect on employee performance in a positive direction. Career development has a significant effect on employee performance in a positive direction. Conclusion - The conclusion of this study, that the tree hypotheses proposed are accepted, namely talent management has a significant effect on employee performance in a positive direction. Career development has a significant effect on employee performance in a positive direction. Talent management and carrer development has a significant effect on employee performance in a positive direction. Research implications - This research can contribute to organizations on how to improve employee performance through talent management and career development